Mineral-organic-phosphorus composite material as well as preparation method and application thereof
By preparing mineral-organic-phosphorus composite materials, the problem of the lack of effect in the prior art when treating multi-component heavy metal contaminated red soil is solved, and efficient heavy metal adsorption and fixation and soil improvement effects are achieved.
Patent Information
- Application Number
- CN202411864128.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-25
AI Technical Summary
The prior art is not ideal when dealing with red soil contaminated by multi-component heavy metals, and its adsorption and fixation ability to heavy metals is insufficient.
Mineral-organic-phosphorus composite materials are used to prepare mineral passivating agents by wet ball milling and baking, and mixed with humic acid and water-soluble phosphate to form composite materials with high adsorption and fixation capabilities.
It significantly improves the adsorption and fixation ability of multiple metals, reduces the bioavailability and migration of heavy metals, improves the structure and fertility of the soil, and enhances the natural buffering ability of the soil.
Smart Images

Figure CN119685031A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of soil remediation, and in particular relates to a mineral-organic-phosphorus composite material and a preparation method and application thereof. Background Art
[0002] Intensive cultivation, excessive use of chemical fertilizers, and acid deposition from chemical weathering have had a significant impact on the basic ions (such as K + 、Na + , Ca 2+ and Mg 2+ ), Si and P. The lack of mineral nutrients accelerates the evolution of soil clay minerals, causing the mineral structure of the soil to gradually change from illite, chlorite and vermiculite (2:1:1 type clay minerals) to montmorillonite (2:1 type clay minerals), and finally to form kaolinite (1:1 type clay minerals) and weathering residues (such as gibbsite and iron oxides). Compared with 2:1 type clay minerals, 1:1 type clay minerals such as kaolinite have lower cation exchange capacity (CEC), resulting in a decrease in the adsorption and retention capacity of nutrients and heavy metals.
[0003] At present, the treatment methods for heavy metal pollution such as cadmium (Cd), lead (Pb) and zinc (Zn) in soil are mainly divided into three categories: physical methods (such as soil replacement, electrodynamic remediation, thermal desorption), biological methods (such as phytoremediation, microbial remediation) and chemical methods (such as chemical passivation, leaching). Among them, in-situ chemical passivation technology is regarded as a green and promising method for the remediation of heavy metal contaminated soil due to its economy, stability and environmental protection. At present, passivation materials are mainly used to treat soils contaminated by a single heavy metal. In soils contaminated by multiple components of heavy metals, the interaction between different heavy metals at the solid-liquid interface of the soil (such as competitive relationship) will change their mobility and bioavailability, making the existing passivation materials not ideal for the effective remediation of soils contaminated by multiple components of heavy metals.
[0004] Prior art CN113522230A discloses a method for preparing a mineral adsorbent, which is obtained by wet-grinding illite, wollastonite, gypsum, dolomite and calcium carbonate and then roasting them. This mineral adsorbent is derived from natural soil, is environmentally friendly, and shows a high removal efficiency when treating cadmium and lead solutions, and is suitable for the restoration of heavy metal-contaminated water bodies. However, when the above-mentioned mineral adsorbent is used in red soil, there is a problem of insufficient adsorption and fixation capacity for heavy metals. Summary of the invention
[0005] In view of this, the present invention provides a mineral-organic-phosphorus composite material and a preparation method and application thereof. The mineral-organic-phosphorus composite material provided by the present invention can efficiently repair red soil polluted by multiple metal complexes and has excellent adsorption and fixation capabilities for heavy metals.
[0006] In order to solve the above technical problems, the present invention provides a method for preparing a mineral-organic-phosphorus composite material, comprising the following steps:
[0007] The mineral raw materials are wet ball-milled and then roasted to obtain a mineral passivator; the mineral raw materials include, by mole fraction, 1 to 3 parts of illite, 0.5 to 2 parts of wollastonite, 0.5 to 2 parts of gypsum, 2 to 4 parts of dolomite, and 0 to 20 parts of calcium carbonate;
[0008] The mineral passivator, humic acid, water-soluble phosphate and water are mixed and then aged and crystallized to obtain a mineral-organic-phosphorus composite material; the mass ratio of the mineral passivator to the humic acid is 1:0.1-7; the content of phosphorus in the mixture of the mineral passivator, humic acid and water-soluble phosphate is 1-16wt%.
[0009] Preferably, the mixing comprises: subjecting the mineral passivator, humic acid and water to a first wet ball milling to obtain a first ball milling mixture; and subjecting the first ball milling mixture and water-soluble phosphate to a second wet ball milling.
[0010] Preferably, the ball milling beads used in the first wet ball milling and the second wet ball milling respectively include large ball milling beads, medium ball milling beads and small ball milling beads;
[0011] The diameter of the large ball milling beads is 1.3-2 cm, the diameter of the medium ball milling beads is 0.8-1.2 cm, and the diameter of the small ball milling beads is 0.1-0.6 cm;
[0012] The ratio of the number of the large ball milling beads to the number of the medium ball milling beads is 1:0.5-2, and the ratio of the number of the large ball milling beads to the number of the small ball milling beads is 1:0.5-2;
[0013] The ball-to-material ratios of the first wet ball milling and the second wet ball milling are independently 3 to 6:15 g.
[0014] Preferably, the rotation speed of the first wet ball milling is 140 to 340 r / min, and the time of the first wet ball milling is 0.6 to 2.1 h;
[0015] The rotation speed of the second wet ball mill is 140-340 r / min, and the time of the second wet ball mill is 0.3-2.3 h.
[0016] Preferably, the aging crystallization temperature is 50-100° C. and the time is 8-25 hours.
[0017] Preferably, the wet ball milling comprises: subjecting the mineral raw material and water to a third wet ball milling.
[0018] Preferably, the mass ratio of the mineral raw material to water is 1:0.2-0.9;
[0019] The third wet ball milling beads include large ball milling beads, medium ball milling beads and small ball milling beads;
[0020] The diameter of the large ball milling beads is 1.3-2 cm, the diameter of the medium ball milling beads is 0.8-1.2 cm, and the diameter of the small ball milling beads is 0.1-0.6 cm;
[0021] The ratio of the number of the large ball milling beads to the number of the medium ball milling beads is 1:0.5-2, and the ratio of the number of the large ball milling beads to the number of the small ball milling beads is 1:0.5-2;
[0022] The ball-to-material ratio of the third wet ball mill is 3 to 6:15 g;
[0023] The rotation speed of the third wet ball milling is 140-340 r / min, and the time of the third wet ball milling is 0.3-2.3 h.
[0024] Preferably, the calcination temperature is 950-1150° C., and the holding time is 0.6-2.1 h.
[0025] The present invention also provides a mineral-organic-phosphorus composite material prepared by the preparation method described in the above technical solution.
[0026] The present invention also provides the use of the mineral-organic-phosphorus composite material described in the above technical solution in repairing heavy metal contaminated soil.
[0027] The preparation method of the mineral-organic-phosphorus composite material provided by the present invention, during the wet ball milling process of the mineral raw material, the continuous impact and friction of the ball milling medium on the mineral particles causes partial disintegration of the crystal structure, so that the crystal structure of the mineral raw material is amorphous and the lattice is deformed, thereby improving the physical and chemical activity of the mineral. By adding a mineralizer (gypsum), the melting point of the system can be reduced, the disordered transformation of potassium-containing rocks can be promoted, and its reaction activity can be enhanced; the introduction of alkaline earth metal cations (Ca) with a smaller radius can reduce the melting point of the system, promote the disordered transformation of potassium-containing rocks, and enhance its reaction activity. 2+ and Mg 2+ ) to replace K in the lattice structure of illite + . SO4, an anion with a higher electronegativity 2- , which can release the K + This leads to the destruction of the chemical balance of the whole system. In order to restore the balance, the illite further decomposes and releases more SiO2, which combines with CaO to form CaSiO4 again. At the same time, during the activation reaction (roasting), the Al in the illite 3+ Si in wollastonite (CaSiO3) 4+Replacement causes a large amount of destruction of the illite structure. Silicon alcohol and aluminum alcohol functional groups are formed in the mineral passivator obtained by roasting, thereby increasing the reactivity of Al and Si. Humic acid is rich in organic active groups, such as carboxyl and hydroxyl groups, and has a high affinity and selectivity for heavy metal ions, effectively promoting the precipitation and chelation of heavy metals. Phosphates can improve the efficiency of repairing heavy metals, provide phosphorus nutrients, increase soil fertility, and enhance the electron transfer efficiency and heavy metal precipitation capacity of the material. The present invention introduces humic acid and water-soluble phosphates for aging and crystallization, which can further activate the potassium and silicon components in illite, promote the structural reorganization of the mineral components and organic components in the mixture, form a more stable crystal structure, and enhance the adsorption and fixation capacity of the mineral-organic-phosphorus composite material for heavy metals.
[0028] The present invention also provides a mineral-organic-phosphorus composite material prepared by the preparation method described in the above technical solution. The mineral-organic-phosphorus composite material provided by the present invention is applied to red soil contaminated by heavy metals (such as cadmium, lead, and zinc), which can reduce the biological effectiveness and mobility of the composite heavy metals by increasing the soil pH value, increasing the effective nutrient content of the soil, increasing the cation exchange capacity (CEC), and expanding the specific surface area; the active binding sites of the mineral-organic-phosphorus composite material are used to promote the capture, chelation, π-heavy metal interaction, chemical precipitation, and ion exchange of heavy metal ions, effectively reducing the effective state content of heavy metals and enhancing their stability.
[0029] The application of mineral-organic-phosphorus composite materials significantly changed the chemical form of heavy metal ions in red soil, reducing the toxicity and mobility of heavy metals. The mineral nutrients provided by the mineral-organic-phosphorus composite materials promoted the transformation of kaolinite in red soil to illite-vermiculite mixed layers, increasing the adsorption and fixation capacity of red soil for heavy metals. In addition, it also increased the pH value and cation exchange capacity of red soil, strengthened the natural buffering capacity of the soil, and restored the original ecological nature of red soil.
[0030] The test results of the examples show that the mineral-organic-phosphorus composite material provided by the present invention can effectively reduce the bioavailability and mobility of cadmium, lead and zinc in composite polluted red soil, and improve soil fertility and structural stability. Specifically, it improves soil pH and enhances cation exchange capacity, promotes the transformation of kaolinite into 2:1 type clay minerals, and enhances the adsorption and fixation capacity of red soil for heavy metals.
[0031] M-HA-P is rich in effective mineral nutrients such as potassium ions, calcium ions, magnesium ions, sodium ions, sulfur ions, silicon ions and phosphorus ions, which are of great significance to improving the fertility of agricultural soil. At the same time, lignite humic acid (HA) in the mineral-organic-phosphorus composite material is a substance rich in organic matter, which can directly increase the organic matter content in red soil, thereby improving soil structure and enhancing soil fertility.
[0032] The mineral-organic-phosphorus composite material provided by the present invention can not only effectively repair soil contaminated by heavy metal compounds, but also efficiently supplement nutrients for red soil, improve the texture of red soil, and control the problem of cadmium, lead, and zinc compound pollution. It also has the advantages of low cost, good effect, and environmental friendliness, and is of great significance for improving soil quality and sustainable agricultural development. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a graph showing the effect of the mineral passivator and the mineral-organic-phosphorus composite material on the chemical forms of Cd in red soil in Example 1;
[0034] Figure 2 This is a graph showing the effect of the mineral passivator and the mineral-organic-phosphorus composite material on the chemical form of Pb in red soil in Example 1;
[0035] Figure 3 This is a graph showing the effect of the mineral passivator and the mineral-organic-phosphorus composite material on the chemical form of Zn in red soil in Example 1;
[0036] Figure 4 This is a graph showing the effects of the mineral passivator and the mineral-organic-phosphorus composite material on organic matter, available potassium and available phosphorus in red soil in Example 1;
[0037] Figure 5 This is a graph showing the effects of the mineral passivator and the mineral-organic-phosphorus composite material on the pH value, CEC, exchangeable base ions and base saturation in red soil in Example 1;
[0038] Figure 6 This is a graph showing the effects of the mineral passivator and the mineral-organic-phosphorus composite material on the exchangeable acid, acid-base buffer capacity, base production and available silicon in red soil in Example 1;
[0039] Figure 7 is the relationship between the exchangeable acid consumption of red soil and the release of silicon / exchangeable base ions in Example 1;
[0040] Figure 8 The X-ray diffraction spectra of the composite polluted red soil and the red soil treated with the mineral passivator and the mineral-organic-phosphorus composite material in Example 1 respectively; the results of the influence of the clay mineral components of the red soil after different treatments;
[0041] Fig. 9 The effect of the mineral passivator and the mineral-organic-phosphorus composite material on the toxicity of heavy metals in red soil in Example 1;
[0042] Fig.10The SEM images (a-c) and EDS spectra (d) of the composite polluted red soil and the red soil treated with the mineral passivator and the mineral-organic-phosphorus composite material in Example 1 respectively;
[0043] Fig.11 FTIR spectra of composite polluted red soil and red soil treated with the mineral passivator and mineral-organic-phosphorus composite material prepared in Example 1;
[0044] Fig.12 XPS spectra of composite polluted red soil and red soil treated with the mineral passivator and mineral-organic-phosphorus composite material prepared in Example 1; fitted high-resolution spectra of Cd3d, Pb4f, Zn2p and O1s;
[0045] Fig.13 Fitted high-resolution spectra of C1s, K2p, Ca2p, Mg1s, Si2p and P2p of composite contaminated red soil and red soil treated with the mineral passivator and mineral-organic-phosphorus composite material prepared in Example 1. DETAILED DESCRIPTION
[0046] The present invention provides a method for preparing a mineral-organic-phosphorus composite material, comprising the following steps:
[0047] The mineral raw materials are wet ball-milled and then roasted to obtain a mineral passivator; the mineral raw materials include, by mole fraction, 1 to 3 parts of illite, 0.5 to 2 parts of wollastonite, 0.5 to 2 parts of gypsum, 2 to 4 parts of dolomite, and 0 to 20 parts of calcium carbonate;
[0048] The mineral passivator, humic acid, water-soluble phosphate and water are mixed and then aged and crystallized to obtain a mineral-organic-phosphorus composite material; the mass ratio of the mineral passivator to the humic acid is 1:0.1-7; the content of phosphorus in the mixture of the mineral passivator, humic acid and water-soluble phosphate is 1-16wt%.
[0049] In the present invention, unless otherwise specified, all materials are conventional commercially available products.
[0050] The invention performs wet ball milling on the mineral raw material and then roasts it to obtain the mineral passivating agent.
[0051] In terms of molar fractions, the mineral raw materials include: 1 to 3 parts of illite, which can be 1 part, 1.5 parts, 2 parts, 2.5 parts or 3 parts in a specific embodiment; 0.5 to 2 parts of wollastonite, which can be 0.5 parts, 1 parts, 1.5 parts or 2 parts in a specific embodiment; 0.5 to 2 parts of gypsum, which can be 0.5 parts, 1 parts, 1.5 parts or 2 parts in a specific embodiment; 2 to 4 parts of dolomite, which can be 2 parts, 2.5 parts, 3 parts, 3.5 parts or 4 parts in a specific embodiment; 0 to 20 parts of calcium carbonate, which can be 0 parts, 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts in a specific embodiment. In the present invention, the particle size of the mineral raw material is preferably ≤75 μm, and the water content of the mineral raw material is preferably ≤3%, more preferably 0 to 3%, and further preferably 1 to 2%.
[0052] Illite is a mineral containing a large amount of silicates, which is widely distributed around the world and is considered to be an environmentally friendly and potentially sustainable resource due to its origin in pristine soil. However, the application of illite in treating heavy metal pollution is limited by its inactivated potassium and silicon components and low remediation effect.
[0053] In the present invention, the wet ball milling preferably comprises: subjecting the mineral raw material and water to a third wet ball milling. In the present invention, the mineral raw material is preferably obtained by grinding illite, wollastonite, gypsum, dolomite and calcium carbonate separately and then sieving, and mixing the materials under the sieves. In the present invention, the grinding is preferably carried out in a planetary ball mill. In the present invention, the size of the sieved screen is preferably 200 to 450 meshes, and in a specific embodiment, it can be 200 mesh, 250 mesh, 300 mesh, 350 mesh or 400 mesh.
[0054] In the present invention, the water preferably includes ultrapure water. In the present invention, the mass ratio of the mixed powder to water is preferably 1:0.2-0.9, and in specific embodiments it can be 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8 or 1:0.9.
[0055] In the present invention, the third wet ball milling grinding beads are preferably zirconia grinding beads; the third wet ball milling grinding beads preferably include large ball milling beads, medium ball milling beads and small ball milling beads; the diameter of the large ball milling beads is preferably 1.3-2 cm, and in a specific embodiment, it can be 1.3 cm, 1.5 cm, 1.8 cm or 2 cm; the diameter of the medium ball milling beads is preferably 0.8-1.2 cm, and in a specific embodiment, it can be 0.8 cm, 1 cm or 1.2 cm; the diameter of the small ball milling beads is preferably 0.1-0.6 cm, and in a specific embodiment, it can be 0.1 cm, 0.3 cm, 0.5 cm or 0.6 cm. In the present invention, the number ratio of the large ball milling beads to the medium ball milling beads is preferably 1:0.5-2, and in specific embodiments, it can be 1:0.5, 1:1, 1:1.5 or 1:2; the number ratio of the large ball milling beads to the small ball milling beads is preferably 1:0.5-2, and in specific embodiments, it can be 1:0.5, 1:1, 1:1.5 or 1:2. In the present invention, the ball-to-material ratio of the third wet ball milling is preferably 3-6:15g, and in specific embodiments, it can be 3:15g, 4:15g, 5:15g, 6:15g. In the present invention, the rotation speed of the third wet ball milling is preferably 140-340 r / min, and in a specific embodiment it can be 140 r / min, 200 r / min, 250 r / min, 300 r / min or 340 r / min; the time of the third wet ball milling is preferably 0.3-2.3 h, and in a specific embodiment it can be 0.3 h, 0.5 h, 1 h, 1.5 h, 2 h or 2.3 h.
[0056] During the wet ball milling process, mineral particles (illite, wollastonite, gypsum, dolomite and calcium carbonate) are not only physically crushed, but also undergo amorphization and lattice distortion of the crystal structure. These changes are due to the continuous impact and friction of the ball milling beads on the mineral particles, which leads to partial destruction of the crystal structure, the formation of amorphous regions and lattice distortion, and thus increases the chemical activity of the mineral. The present invention optimizes the structure and performance of the mineral passivator by controlling the size of the ball milling beads and the ball-to-material ratio, adjusting the impact force and grinding effect. The present invention ensures that the material is fully impacted and rubbed by limiting the appropriate ball-to-material ratio, thereby accelerating the activation reaction process during the roasting process; at the same time, a reasonable ball milling method can reduce energy consumption and improve production efficiency.
[0057] In the present invention, the third wet ball milling preferably further includes: drying the material after the third wet ball milling; the drying temperature is preferably 80-120°C, and in specific embodiments it can be 80°C, 90°C, 100°C, 110°C or 120°C; the drying time is preferably 5-8h, and in specific embodiments it can be 5h, 6h, 7h or 8h.
[0058] In the present invention, the calcination temperature is preferably 950-1150°C, and in specific embodiments it can be 950°C, 1000°C, 1100°C or 1150°C; the heating rate to the calcination temperature is preferably 10-30°C / min, and in specific embodiments it can be 10°C / min, 15°C / min, 20°C / min, 25°C / min or 30°C / min; the holding time for calcination is preferably 0.6-2.1h, and in specific embodiments it can be 0.6h, 1h, 1.5h, 2h or 2.1h.
[0059] In the present invention, gypsum (CaSO4) can significantly reduce the activation energy required for the decomposition of dolomite and calcium carbonate. In the range of 650 to 790°C during the roasting temperature rise, dolomite (CaMg(CO3)2) and calcium carbonate (CaCO3) are decomposed into CaO, MgO and CO2. After the dolomite and calcium carbonate are completely decomposed, the system undergoes an activation reaction in the range of 790 to 1000°C, accompanied by the generation of new minerals, such as illite ((K, Na)(Al, Mg, Fe)2(Si 3.l Al 0.9 ) 10 (OH)2) releases SiO2 in the molten state and combines with CaO to form Ca2SiO4, while alkali metal cations with relatively small ionic radius (such as Ca 2+ and Mg 2+ ) enters the lattice, replacing the K in the illite lattice structure + , the more electronegative anion SO4 2- The released K + The capture and fixation leads to the destruction of the chemical balance of the whole system. In order to restore the balance, the illite further decomposes and releases more SiO2, which combines with calcium oxide to form Ca2SiO4 again. At the same time, during the activation reaction (roasting), the Al in the illite 3+ Si in wollastonite (CaSiO3) 4+ Replacement leads to a large amount of destruction of the illite structure. Silanol and aluminol functional groups are formed in the mineral passivator obtained after roasting. The phase composition of the mineral passivator includes CaAl2Si2O8·4H2O, SiO2, KAlSiO4, K2Ca(SO4)2·H2O, Mg2Al(OH)7, Ca3Al2(SiO4)3, CaSO4, Ca4(AlSi2O6)8·16H2O and Ca2SiO4.
[0060] In the present invention, after the calcination, the method preferably further comprises: cooling the calcined product and then crushing it to obtain the mineral passivator. In the present invention, the cooling method preferably comprises air cooling, and the temperature after the cooling is preferably 20 to 35°C, more preferably 25 to 30°C. In the present invention, the particle size of the mineral passivator is preferably 200 to 450 mesh, and in a specific embodiment, it can be 200 mesh, 250 mesh, 300 mesh, 350 mesh, 400 mesh or 450 mesh.
[0061] After obtaining the mineral passivator, the present invention mixes the mineral passivator, humic acid, water-soluble phosphate and water, and then matures and crystallizes to obtain a mineral-organic-phosphorus composite material; the mass ratio of the mineral passivator to the humic acid is 1:0.1-7; the content of phosphorus in the mixture of the mineral passivator, humic acid and water-soluble phosphate is 1-16wt%.
[0062] In the present invention, the humic acid preferably includes lignite humic acid; the particle size of the humic acid is preferably ≤75 μm; the moisture content of the humic acid is preferably ≤3%, more preferably 0-3%, and further preferably 1-2%. In the present invention, the mass ratio of the mineral passivator and humic acid is 1:0.1-7, and in specific embodiments it can be 1:0.1, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6 or 1:7. Lignite humic acid (HA) contains a large number of active groups, such as carboxyl and hydroxyl groups, which can adsorb cations, thereby enhancing the CEC of red soil. In addition, mineral components such as CaO and MgO produced during the roasting process also help to improve the CEC of the soil. HA itself has a complex molecular structure and a large specific surface area. When it is mixed with a mineral passivator, it can further increase the specific surface area of the overall material, providing more active sites for the adsorption of heavy metals in the soil.
[0063] In the present invention, the water-soluble phosphate is preferably one or more of potassium dihydrogen phosphate, dipotassium hydrogen phosphate, potassium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate and ammonium phosphate; the water content of the water-soluble phosphate is preferably ≤3%, more preferably 0-3%, and further preferably 1-2%.
[0064] The present invention introduces soluble phosphates (such as potassium dihydrogen phosphate, dipotassium hydrogen phosphate, potassium phosphate) to provide K and P nutrients, improve soil fertility, enhance the electron transfer efficiency and heavy metal precipitation capacity of the passivator, and improve the efficiency of heavy metal repair.
[0065] In the present invention, the content of phosphorus in the mixture of the mineral passivator, humic acid and water-soluble phosphate is 1 to 16 wt %, and in specific embodiments it can be 1%, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 15% or 16%.
[0066] In the present invention, the water preferably comprises ultrapure water. In the present invention, the mass ratio of the total mass of the mineral passivator and humic acid to water is preferably 1:0.2-0.9, and in specific embodiments may be 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8 or 1:0.9.
[0067] In the present invention, the mixing preferably includes: subjecting the mineral passivator, humic acid and water to a first wet ball milling to obtain a first ball milling mixture; and subjecting the first ball milling mixture and a water-soluble phosphate to a second wet ball milling.
[0068] In the present invention, the first wet ball milling grinding beads are preferably zirconia grinding beads; the first wet ball milling grinding beads preferably include large ball milling beads, medium ball milling beads and small ball milling beads; the diameter of the large ball milling beads is preferably 1.3-2 cm, and in specific embodiments, it can be 1.3 cm, 1.5 cm, 1.8 cm or 2 cm; the diameter of the medium ball milling beads is preferably 0.8-1.2 cm, and in specific embodiments, it can be 0.8 cm, 1 cm or 1.2 cm; the diameter of the small ball milling beads is preferably 0.1-0.6 cm, and in specific embodiments, it can be 0.1 cm, 0.3 cm, 0.5 cm or 0.6 cm. In the present invention, the number ratio of the large ball milling beads to the medium ball milling beads is preferably 1:0.5-2, and in specific embodiments, it can be 1:0.5, 1:1, 1:1.5 or 1:2; the number ratio of the large ball milling beads to the small ball milling beads is preferably 1:0.5-2, and in specific embodiments, it can be 1:0.5, 1:1, 1:1.5 or 1:2. In the present invention, the ball-to-material ratio of the first wet ball milling is preferably 3-6:15g, and in specific embodiments, it can be 3:15g, 4:15g, 5:15g, 6:15g. In the present invention, the rotation speed of the first wet ball milling is preferably 140-340 r / min, and in specific embodiments it can be 140 r / min, 200 r / min, 250 r / min, 300 r / min or 340 r / min; the time of the first wet ball milling is preferably 0.6-2.1 h, and in specific embodiments it can be 0.6 h, 0.8 h, 1 h, 1.5 h, 2 h or 2.1 h.
[0069] In the present invention, after the first wet ball milling, it is preferred that the method further comprises: drying and sieving the material after the first wet ball milling in sequence to obtain a first ball milling mixture. In the present invention, the drying temperature is preferably 80-120°C, and in a specific embodiment it can be 80°C, 90°C, 100°C, 110°C or 120°C; the drying time is preferably 5-8h, and in a specific embodiment it can be 5h, 6h, 7h or 8h. In the present invention, the size of the sieve is preferably 200-450 mesh, and in a specific embodiment it can be 200 mesh, 250 mesh, 300 mesh, 350 mesh, 400 mesh or 450 mesh, and the material under the sieve is used.
[0070] In the present invention, the second wet ball milling dispersant is preferably water, and the water preferably includes ultrapure water. The mass ratio of the total mass of the mixture of the first ball milling mixture and the water-soluble phosphate to the mass ratio of water is preferably 1:0.2-0.9, and in specific embodiments it is 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8 or 1:0.9. In the present invention, the second wet ball milling grinding beads are preferably zirconia grinding beads; the second wet ball milling grinding beads preferably include large ball milling beads, medium ball milling beads and small ball milling beads; the diameter of the large ball milling beads is preferably 1.3-2 cm, and in a specific embodiment, it can be 1.3 cm, 1.5 cm, 1.8 cm or 2 cm; the diameter of the medium ball milling beads is preferably 0.8-1.2 cm, and in a specific embodiment, it can be 0.8 cm, 1 cm or 1.2 cm; the diameter of the small ball milling beads is preferably 0.1-0.6 cm, and in a specific embodiment, it can be 0.1 cm, 0.3 cm, 0.5 cm or 0.6 cm. In the present invention, the number ratio of the large ball milling beads to the medium ball milling beads is preferably 1:0.5-2, and in specific embodiments, it can be 1:0.5, 1:1, 1:1.5 or 1:2; the number ratio of the large ball milling beads to the small ball milling beads is preferably 1:0.5-2, and in specific embodiments, it can be 1:0.5, 1:1, 1:1.5 or 1:2. In the present invention, the ball-to-material ratio of the second wet ball milling is preferably 3-6:15g, and in specific embodiments, it can be 3:15g, 4:15g, 5:15g, 6:15g. In the present invention, the rotation speed of the second wet ball milling is preferably 140-340 r / min, and in specific embodiments it can be 140 r / min, 200 r / min, 250 r / min, 300 r / min or 340 r / min; the time of the second wet ball milling is preferably 0.3-2.3 h, and in specific embodiments it can be 0.3 h, 0.5 h, 1 h, 1.5 h, 2 h or 2.3 h.
[0071] In the present invention, the temperature of the aging crystallization is preferably 50-100°C, and in specific embodiments it can be 50°C, 60°C, 70°C, 80°C, 90°C or 100°C; the time of the aging crystallization is preferably 8-25h, and in specific embodiments it can be 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h or 25h.
[0072] The present invention not only improves the physical and chemical properties of the mineral-organic-phosphorus composite material through the aging and crystallization process, but also enhances its function in soil remediation. The specific changes are as follows: Structural reorganization: During the aging and crystallization process, the mineral components and organic components in the mixture of the mineral passivator, humic acid and water-soluble phosphate undergo structural reorganization to form a more stable crystal structure. Formation of new mineral phases: During the aging and crystallization process, due to the control of temperature and time, the mineral components in the mixed system will undergo chemical reactions to generate new mineral phases. For example, the silicates and aluminosilicates in the mineral passivator (M) will react with humic acid and water-soluble phosphate to form new phosphorus-containing mineral phases. Enhanced cation exchange capacity (CEC): The combination of the newly formed mineral phase and organic matter during the aging and crystallization process increases the cation exchange capacity (CEC) of the mineral-organic-phosphorus composite material, which is crucial for enhancing the soil's ability to fix heavy metal ions. Improved stability of the mineral-organic-phosphorus composite material: The aging and crystallization process improves the thermal stability and chemical stability of the mineral-organic-phosphorus composite material, so that it can play a more effective role in the soil environment and reduce the performance degradation caused by environmental changes. Enhance soil fertility: During the ripening and crystallization process, the addition of nutrients such as water-soluble phosphates provides additional P nutrients to the mineral-organic-phosphorus composite material. These nutrients are slowly released in the soil, enhancing the fertility of the soil.
[0073] In the present invention, the aging and crystallization preferably further comprises: grinding and sieving the solid product after the aging and crystallization in sequence, and the material under the sieve is the mineral-organic-phosphorus composite material.
[0074] The present invention has no special requirements for the grinding, and the conventional method in the art can be used. In the present invention, the aperture of the sieve for sieving can be 200-450 meshes, and in a specific embodiment can be 200 meshes, 250 meshes, 300 meshes, 350 meshes, 400 meshes or 450 meshes.
[0075] The preparation method of the mineral-organic-phosphorus composite material provided by the invention is simple and uses cheap raw materials, thereby greatly reducing the production cost of the mineral-organic-phosphorus composite material.
[0076] The raw materials for preparing the mineral passivator of the present invention include alkaline materials, such as dolomite (CaMg(CO3)2) and calcium carbonate (CaCO3), which decompose to generate calcium oxide (CaO) and magnesium oxide (MgO) during the roasting process. These substances are hydrated to form calcium hydroxide (Ca(OH)2) and magnesium hydroxide (Mg(OH)2), which can neutralize the acidic substances in the soil and increase the soil pH value. At the same time, the silicate or aluminosilicate minerals in the mineral passivator have a certain alkalinity and can react with the H in the red soil. + Reacts to generate SiO3 2- and H2O, further consuming protons in the red soil and increasing the pH value of the red soil. The reduction of exchangeable acid in the red soil is mainly caused by the silicate minerals released by the mineral passivator, and the corresponding alkaline substances play an auxiliary role.
[0077] The lignite humic acid added to the mineral-organic-phosphorus composite material of the present invention is a substance rich in organic matter, which can directly increase the organic matter content in the soil, thereby improving the soil structure and increasing the soil fertility. At the same time, lignite humic acid contains a large number of functional groups, such as carboxyl and phenolic hydroxyl groups, which can adsorb cations, thereby increasing the cation exchange capacity (CEC) of the soil. In addition, mineral components generated during the roasting process, such as calcium oxide and magnesium oxide, also help to improve the CEC of the soil. During the roasting process, the decomposition and recrystallization of natural minerals such as illite will produce minerals with a large specific surface area, which can provide more surface active sites, thereby increasing the specific surface area of the mineral-organic-phosphorus composite material. At the same time, the addition of lignite humic acid also helps to increase the specific surface area of the overall material, because the humic acid molecule has a complex structure and a large surface area. In addition, the mineral nutrients in the mineral-organic-phosphorus composite material can promote the transformation of kaolinite in red soil to 2:1 type clay minerals, and 2:1 type clay minerals have higher CEC and specific surface area. The addition of mineral-organic-phosphorus composites and the transformation of clay minerals increased the specific surface area of the soil.
[0078] The active adsorption sites in the mineral-organic-phosphorus composite material provided by the present invention refer to functional groups, mineral surface active sites, lattice substitution sites, active sites generated by structural destruction, silanol and aluminum alcohol groups. The following is a specific description of the active adsorption sites: 1) Functional groups: lignite humic acid contains active functional groups such as carboxylic acid groups (-COOH), ester groups (-COO-), alcohol groups (-OH) and ether bonds (-O-). These functional groups have high affinity and selectivity and can effectively promote the precipitation and chelation of heavy metals. The phosphate (PO4 3-) functional groups can stably chelate heavy metal ions. 2) Active sites on the mineral surface: During the roasting process, natural minerals such as illite decompose and recrystallize to form minerals with a large specific surface area. The surfaces of these new minerals provide more active sites (such as silicate, aluminate, aluminosilicate and sulfate). The mineral nutrients in the mineral-organic-phosphorus composite materials can promote the transformation of kaolinite into 2:1 type clay minerals. These clay minerals have higher cation exchange capacity (CEC) and specific surface area, providing more active adsorption sites. 3) Lattice substitution: During the roasting process, alkali metal cations with smaller radius (such as Ca 2+ ) enters the illite lattice, replacing K + The active sites generated by this lattice replacement can interact with heavy metal ions. 4) Active sites generated by structural destruction: Si in wollastonite 4+ Replaces Al in illite 3+ , resulting in large-scale destruction of the illite structure, and the resulting active sites can enhance the ability to capture heavy metals. 5) Silanol and aluminol functional groups: Silanol (Si-OH) and aluminol (Al-OH) functional groups are generated in the illite source mineral passivator after calcination and activation. These functional groups can chelate with heavy metal ions.
[0079] The present invention also provides a mineral-organic-phosphorus composite material prepared according to the preparation method described in the above technical solution. In the present invention, the particle size of the mineral-organic-phosphorus composite material is preferably ≤75 μm.
[0080] The mineral-organic-phosphorus composite material prepared by the present invention strengthens the capture, chelation, π-heavy metal cation interaction, chemical precipitation and ion exchange of cadmium, lead and zinc ions by virtue of its numerous active adsorption sites, such as active groups (carboxyl (-COOH), ester group (-COO-), alcohol group (-OH) and ether bond (-O-)), silicate, aluminate, aluminosilicate, phosphate and active potassium, calcium, magnesium and sodium ions on the surface of the mineral. At the same time, after adding the mineral-organic-phosphorus composite material, sulfate reacts with lead ions to generate lead sulfate precipitation, and the interaction between cadmium, zinc ions and iron and manganese oxides in red soil is enhanced. These effects significantly adjust the chemical state of cadmium, lead and zinc in red soil, effectively reduce their bioavailability and mobility, and thus enhance their stability.
[0081] The mineral-organic-phosphorus composite material provided by the present invention achieves multi-faceted improvements on red soil through its specific structure and composition, including increasing pH value, increasing organic matter, enhancing CEC and specific surface area, promoting clay mineral transformation, providing plant nutrients and reducing heavy metal toxicity, thereby improving the ecological safety of the soil and agricultural productivity.
[0082] The present invention also provides the use of the mineral-organic-phosphorus composite material described in the above technical solution in remediating heavy metal contaminated soil. In the present invention, the soil preferably includes red soil.
[0083] The mineral-organic-phosphorus composite material prepared by the present invention has the characteristics of slightly alkalinity, high effective nutrient content, high cation exchange capacity and large specific surface area. The mineral-organic-phosphorus composite material with unique structure and composition is used for the restoration of red soil, which can optimize the pH value of red soil, enhance the cation exchange performance, improve the acid-base buffering capacity, and promote the transformation of kaolinite to illite-vermiculite mixed layer, strengthen the adsorption and fixation effect of red soil on cadmium, lead and zinc, and significantly promote the transformation of kaolinite to illite-vermiculite mixed layer, while reducing the bioavailability and mobility of cadmium, lead and zinc, thereby enhancing the natural regulation capacity of soil, and realizing all-round improvement of red soil. The material can significantly reduce the bioavailability and mobility of heavy metals in red soil, improve the fertility and structural stability of red soil, help red soil to recover to its original ecological balance state, and improve the agricultural productivity of soil.
[0084] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0085] Example 1
[0086] (1) Illite, wollastonite, gypsum, dolomite and calcium carbonate were ground into powders using a planetary ball mill and sieved through a 200-mesh sieve; the powdered illite, wollastonite, gypsum, dolomite and calcium carbonate were mixed in a molar ratio of 2:1:1:3:9, and the mixed powder was added to a zirconia ball mill jar (with an outer diameter of 10.5 cm and an inner diameter of 15 g) together with zirconia ball mill beads of different particle sizes (the number of ball mill beads with particle sizes of 1.5 cm, 1 cm and 0.5 cm was in a ratio of 1:1:1, and the ball-to-material ratio was 4 beads:15 g). 9cm, external height 10.8cm, internal height 8.8cm); ultrapure water (the mass ratio of ultrapure water to mixed powder is 0.4:1) is added to the ball mill jar and fully stirred, and then the ball mill is milled at a speed of 200r / min for 0.5h; the ball-milled material is dried at 105°C in a muffle furnace for 5h, heated to 1000°C at a heating rate of 20°C / min, and then heat-preserved and roasted for 1h; the roasted material is air-cooled to 25°C, crushed and sieved through a 200-mesh sieve, and the material under the sieve is a mineral passivator (M);
[0087] (2) The mineral passivator and lignite humic acid were added into a zirconia ball milling jar at a mass ratio of 1:1.5 together with zirconia ball milling beads of different particle sizes (ball milling beads with particle sizes of 1.5 cm, 1 cm, and 0.5 cm, with a number ratio of 1:1:1, and a ball-to-material ratio of 4:15 g). Ultrapure water accounting for 50% of the total mass of the mineral passivator and lignite humic acid was then added, and the mixture was ball milled at a speed of 190 r / min for 1 h, then taken out, dried at 105° C. for 5 h, ground, and sieved through a 200-mesh sieve. The material under the sieve was the first ball milling mixture; the first ball milling mixture and potassium dihydrogen phosphate (mineral passivator) were mixed and the mixture was sieved. The mixture of the first ball-milling mixture and the potassium dihydrogen phosphate (the mass percentage of phosphorus element in the mixture is 6%) and zirconium oxide ball milling beads of different particle sizes (the number ratio of ball milling beads with particle sizes of 1.5 cm, 1 cm and 0.5 cm is 1:1:1, and the ball-to-material ratio is 4:15g) are added into a zirconium oxide ball milling jar, and then ultrapure water accounting for 50% of the total mass of the first ball-milling mixture and the potassium dihydrogen phosphate is added, and wet ball milling is carried out at a speed of 190r / min for 0.5h, and the mixture is aged and crystallized at 70°C for 9h, ground, and passed through a 200-mesh sieve. The material under the sieve is a mineral-organic-phosphorus composite material (M-HA-P).
[0088] The physical and chemical properties of the mineral passivator and the mineral-organic-phosphorus composite material prepared in Example 1 were tested, and the results obtained are shown in Table 1.
[0089] Table 1 Physical and chemical properties of mineral passivators and mineral-organic-phosphorus composite materials in Example 1
[0090] project M M-HA-P pH 12.0 9.47 Organic matter (g / kg) 1.45 633 Cation exchange capacity CEC (cmol / kg) 5.20 182 <![CDATA[Specific surface area (m 2 / g)]]> 2.36 5.23 Average pore size (nm) 4.82 25.8 <![CDATA[Average pore volume (cm 3 / g)]]> 0.003 0.03 <![CDATA[Particle diameter D 10 (μm)]]> 5.86 3.84 <![CDATA[Particle diameter D 50 (μm)]]> 32.6 33.7 <![CDATA[Particle diameter D 90 (μm)]]> 71.4 68.2
[0091] Compared with M (pH = 12.0), the pH value of M-HA-P (pH = 9.47) decreased significantly, indicating that the alkalinity of M-HA-P was weakened. This is mainly because the dissolved potassium dihydrogen phosphate is acidic, and phosphate participates in the hydration recrystallization process of M, resulting in a decrease in pH. However, the alkaline metal ions and silicon ions in M-HA-P, especially calcium ions and magnesium ions, undergo efficient ion exchange reactions with hydrogen ions and aluminum ions in red soil to generate hydroxide ions, thereby neutralizing the acidity of red soil and promoting the natural increase in pH, reducing the harmfulness and mobility of cadmium, lead and zinc. Silicon ions mainly exist in the form of silicate or aluminosilicate minerals, which react with hydrogen ions in red soil to generate silicate ions and water, further consuming protons and increasing pH. The reduction of exchangeable acid in red soil is mainly caused by silicate minerals and their corresponding alkaline components released by mineral-organic-phosphorus composites. Therefore, mineral-organic-phosphorus composites are more suitable for remediation of weakly acidic or neutral heavy metal-contaminated water bodies and red soils.
[0092] Compared with mineral passivators, mineral-organic-phosphorus composite materials showed higher values in organic matter content, cation exchange capacity, specific surface area, average pore size and average pore volume. Specifically, the organic matter concentration of the mineral passivator was 1.45 g / kg, while that of the mineral-organic-phosphorus composite material was as high as 633 g / kg, indicating that the mineral-organic-phosphorus composite material can more effectively supplement the organic matter of water bodies and red soil. The cation exchange capacity of the mineral passivator was 5.20 cmol / kg, while that of the mineral-organic-phosphorus composite material was as high as 182 cmol / kg, indicating that the mineral-organic-phosphorus composite material can fix heavy metal ions through more effective ion exchange. The N2 adsorption-desorption results showed that the specific surface area, average pore size and average pore volume of the mineral passivator were 2.36 m 2 / g, 4.82nm and 0.003cm 3 / g, while that of mineral-organic-phosphorus composite materials was 5.23m 2 / g, 25.8nm and 0.03cm 3 / g, indicating that the mineral-organic-phosphorus composite material has stronger adsorption performance. The average pore size of the mineral passivator and the mineral-organic-phosphorus composite material is larger than that of Pb 2+ (0.13nm) and Cd 2+ (0.10nm), which means that these heavy metal ions can penetrate and enter the pore structure of the material. The particle size of mineral passivators and mineral-organic-phosphorus composites (D 10 ~D 90 ) are mainly distributed between 5.86-71.4 μm and 3.84-68.2 μm, respectively. The average particle size (D 50 ) are 32.6 μm and 33.7 μm respectively. This indicates that the particle size of the material is small, which makes the material easy to disperse in aqueous solution and red soil, and provides a larger contact area for heavy metal ions, thereby improving the efficiency of the adsorption and fixation reaction of heavy metal ions.
[0093] Example 2
[0094] A mineral passivator and a mineral-organic-phosphorus composite material were prepared according to the method of Example 1, except that the mass ratio of the mineral passivator to the lignite humic acid was adjusted from 1:1.5 to 1:0.5.
[0095] Example 3
[0096] A mineral passivator and a mineral-organic-phosphorus composite material were prepared according to the method of Example 1, except that the mass ratio of the mineral passivator to the lignite humic acid was adjusted from 1:1.5 to 1:2.
[0097] Example 4
[0098] The mineral passivator and the mineral-organic-phosphorus composite material were prepared according to the method of Example 1, except that the mass percentage of phosphorus in the mixture of the mineral passivator, lignite humic acid and potassium dihydrogen phosphate was adjusted from 6% to 3%.
[0099] Test Case
[0100] Restoration performance of mineral-organic-phosphorus composite materials on red soil
[0101] (1) Experimental methods
[0102] The red soil of farmland with composite pollution in the cadmium, lead and zinc mining area of Yangshuo, Guilin, Guangxi was used as the experimental soil. The composite polluted red soil was sieved through a 10-mesh sieve and divided into several portions, each of which was 5 kg. The mineral passivator (M) and the mineral-organic-phosphorus composite material (M-HA-P) prepared in Example 1 were respectively mixed evenly with the composite polluted red soil at a dosage of 3 wt %; then they were placed in a plastic pot, the water was adjusted to the field water holding capacity of the soil (about 50% soil moisture content), and they were placed in an indoor culture, and water was replenished every 3 days. During the culture period, soil samples were collected regularly for multiple analyses. These analyses included the determination of the basic physical and chemical properties of the red soil, the occurrence forms of heavy metals (cadmium, lead and zinc), organic matter content, effective mineral nutrients (potassium, calcium, magnesium, silicon and phosphorus), pH value, cation exchange capacity (CEC), exchangeable base ion content, exchangeable acid content, acid-base buffer capacity, clay mineral components and heavy metal toxicity levels. In addition, further analysis will be carried out by scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS), Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS). Figure 1 to Figure 6 and Figure 8 to Figure 13 In the figure, CK represents the untreated group, M represents the mineral passivator treated group, and M-HA-P represents the mineral-organic-phosphorus composite material treated group.
[0103] (2) Measurement method
[0104] The determination of heavy metal content in red soil was based on the national industry standards HJ 776-2015 and HJ 803-2016; the occurrence forms of heavy metals were determined using the Tessier five-step continuous extraction method. The mineral nutrients in materials and soil samples were determined according to the standards NY / T1121.15-2006 (available silicon), NY / T 889-2004 (available potassium) and NY / T 1121.7-2014 (available phosphorus), respectively. The pH value and available nitrogen of red soil were determined according to the standards NY / T 1973-2010 and GB / T 17143-2008, respectively. The CEC, organic matter, total phosphorus, total potassium and total nitrogen were determined according to the standards HJ 889-2017, NY / T 1121.6-2006, HJ632-2011, NY / T87-1988 and HJ 717-2014, respectively.
[0105] Soil exchangeable base ions (Ca 2+ Mg 2+ , K + 、Na + ) was extracted with ammonium acetate and determined by atomic absorption spectrophotometry. The specific steps refer to standards NY / T 295-1995 and NY / T 1121.13-2006. Exchangeable acid (H + 、Al 3+ ) was determined by exchange-neutralization titration method, and the specific method was based on standard LY / T 1240-1999. Soil acid-base buffer capacity (pH BC) was determined by CO2-free distilled water extraction method in acid-base titration (doi:10.3969 / j.issn.1000-4440.2020.06.014).
[0106] Base saturation (%) = (total amount of exchangeable base ions / CEC) × 100 (1)
[0107] Alkali production = (pH T -pH CK )×pHBC (2)
[0108] Where, pH T and pH CK Represent the pH values of the treated group and the control group, respectively.
[0109] Clay minerals were extracted by centrifugation and sedimentation techniques. The specific steps for qualitative and quantitative analysis of clay minerals in red soil are as follows: First, aggregates with a particle size of less than 1 mm were extracted from the aqueous suspension by sedimentation. Then, these aggregates were transferred to glass slides and air-dried to obtain naturally oriented sheets (N sheets). Next, the N sheets were placed in ethylene glycol vapor and fumigated and saturated at 55 °C for more than 8 h to obtain ethylene glycol saturated sheets (EG sheets). Then, the EG sheets were treated at a constant temperature at 500 °C for more than 2.5 h to obtain high-temperature sheets (T sheets). Next, the N, EG and T sheet samples were subjected to X-ray powder diffraction (XRD) analysis. The entire experimental operation and XRD analysis were carried out in accordance with the provisions of standard SY / T 5163-2018. The toxicity of heavy metals in red soil was determined using the solid waste toxicity characteristic leaching procedure (TCLP).
[0110] Au / Pd was sprayed on the surface of the test sample to improve its conductivity, and then SEM-EDS was used to obtain images and spectra of the red soil before and after treatment. FTIR was used to measure the infrared spectrum of the red soil before and after treatment. XPS was used to determine the elemental composition and valence state of the red soil surface before and after treatment. XPS test data were analyzed using Advantage software.
[0111] (3) Basic physical and chemical properties of farmland red soil
[0112] The basic physical and chemical properties of the untreated red soil (CK) are shown in Table 2. The determination methods of the relevant indicators have been described in detail in the determination method section of step (2) above. The total nitrogen, total phosphorus and total potassium were 512 mg / kg, 823 mg / kg and 3.26%, respectively. The available nitrogen, available phosphorus and available potassium in the red soil were 17.8 mg / kg, 3.24 mg / kg and 117 mg / kg, respectively. The organic matter and CEC were 24.5 g / kg and 7.11 cmol / kg, respectively. The red soil was slightly acidic (pH 6.53), and the concentrations of Cd, Pb and Zn were 7.90 mg / kg, 1384 mg / kg and 2259 mg / kg, respectively, which were 15.8 times, 8.6 times and 9.0 times the agricultural land soil quality standards, respectively. The concentrations of exchangeable calcium, exchangeable magnesium and available silicon were 5.36 cmol / kg, 1.12 cmol / kg and 1.74 cmol / kg.
[0113] Table 2 Basic physical and chemical properties of farmland red soil
[0114]
[0115]
[0116] (4) Effects and mechanisms of mineral passivators and mineral-organic-phosphorus composite materials on the original ecological restoration of cadmium, lead and zinc contaminated red soil
[0117] (4.1) Effects of mineral passivators and mineral-organic-phosphorus composites on the chemical forms of Cd, Pb, and Zn in red soil
[0118] After adding mineral passivators and mineral-organic-phosphorus composite materials to red soil, the stabilization of cadmium in all experimental groups was significantly improved within 7 days, such as Figure 1 As shown in Figure 2. In just 7 days, the passivation and fixation process of cadmium was almost completed. Moreover, the stabilization effect of each treatment group remained at a high level within 7 to 90 days, which shows that the materials used not only react quickly but also have excellent long-term stability. At 90 days, cadmium in the red soil of the CK group mainly existed in three forms: exchangeable state accounted for 11.8%, carbonate-bound state accounted for 46.9%, and iron-manganese oxidation state accounted for 34.1%. Compared with the CK group, the exchangeable state of cadmium in the red soil decreased by 9.1% after adding M, and the iron-manganese oxidation state and organic state increased by 7.6% and 0.9%. This effect may be due to the formation of complexes between the oxygen-containing functional groups on the surface of M and cadmium, while the silicate / aluminosilicate in M reacted with cadmium to form stable compounds that are insoluble in water. In addition, M can also increase the pH value of the red soil, which helps to form cadmium hydroxide precipitation. The addition of M-HA-P caused the exchangeable and carbonate-bound cadmium in red soil to decrease by 8.4% and 10.0%, respectively, while the ferromanganese oxidized and organic states increased by 14.7% and 2.9%, respectively. This is probably due to the active adsorption sites provided by M-HA-P and the active minerals, active functional groups and ferromanganese oxides in the red soil, which led to the formation of cadmium complexes and chemical precipitates on the surface of M-HA-P. These findings indicate that the composite modification of lignite humic acid and phosphate enhances the ability of mineral passivators to retain cadmium in red soil. In general, the effective state of cadmium and its migration potential can be evaluated by examining the content ratio of exchangeable and carbonate-bound cadmium in red soil. Therefore, these materials all showed a good stabilization effect on cadmium in red soil, and the effect was ranked from strong to weak as M-HA-P>M>CK.
[0119] In just 7 days, the stabilization process of lead in the red soil with the addition of M-HA-P was basically completed. Figure 2As shown. Moreover, the immobilization effect of all treatment groups remained at a high level from 7 to 90 days, which shows that the materials used not only act quickly but also have excellent long-term stability. At 90 days, the lead in the red soil of the CK group mainly existed in four forms: carbonate-bound state accounted for 20.6%, iron-manganese oxidized state accounted for 51.1%, organic state accounted for 12.9%, and residual state accounted for 15.1%. The addition of M caused the carbonate-bound state of lead in the red soil to decrease by 3.5% and the residual state to increase by 2.4%, which may be due to the formation of lead complexes and chemical precipitates on the surface of M. By adding M-HA-P, the exchangeable state, carbonate-bound state and iron-manganese oxidized state of lead in the red soil decreased by 0.2%, 14.2% and 2.9%, respectively, while the organic state and residual state increased by 2.9% and 14.3%, respectively. This is probably because the active functional groups and active minerals in M-HA-P and red soil provide active adsorption sites, which lead complexes and chemical precipitates are formed on the surface of M-HA-P. Therefore, these materials all have a good stabilization effect on lead in red soil, and the effects are ranked from high to low as M-HA-P>M>CK.
[0120] Within 15 days, the passivation process of zinc in the red soil treated with M-HA-P was almost completed. Figure 3 As shown. In addition, the immobilization effect remained stable from 15 to 90 days, which shows that M-HA-P can not only work quickly, but also has excellent long-term stability. At 90 days, the zinc in the red soil of the CK group mainly existed in the iron-manganese oxidation state (49.1%), organic state (14.6%) and residual state (29.4%), while the content of exchangeable state (0.7%) and carbonate-bound state (6.2%) was relatively small. After adding M, the iron-manganese oxidation state of zinc in the red soil decreased by 5.3%, and the residual state increased by 5.8%. After adding M-HA-P, the exchangeable state and carbonate-bound state of zinc in the red soil decreased by 0.4% and 2.0%, respectively, and the iron-manganese oxidation state of zinc increased by 3.4%. Therefore, both M and M-HA-P materials have a good stabilization effect on zinc in red soil, and their immobilization mechanism for zinc may be similar to that for cadmium.
[0121] (4.2) Effects of mineral passivators and mineral-organic-phosphorus composites on organic matter, available K, and effective P in red soil
[0122] In the CK group, the organic matter concentration of red soil was 23.8 g / kg. Figure 4As shown. When M-HA-P was added, the organic matter content of the red soil increased by 33.2%. In the CK group, the available K concentration of the red soil was 0.12g / kg, and after the application of M and M-HA-P, the available K content increased by 170% and 1178%, respectively. In the CK group, the effective P concentration of the red soil was 3.46mg / kg, and after the addition of M-HA-P, the effective P content surged by 1465%. These data show that the application of M and M-HA-P materials significantly increased the levels of organic matter, available K, and available P in the red soil.
[0123] (4.3) Effects of mineral passivators and mineral-organic-phosphorus composites on protons, base ions and available silicon in red soil
[0124] In the CK group, the initial pH value of the red soil was 6.67. Figure 5 As shown. When M and M-HA-P were applied, the pH of the red soil increased by 1.72 and 1.54 units, respectively. This change was mainly due to the fact that these materials themselves have alkaline or weak alkaline properties and are rich in alkaline base cations such as calcium and magnesium. These cations exchanged with hydrogen and aluminum ions in the red soil to generate a large number of hydroxide ions, which effectively neutralized the acidity of the soil and significantly increased the pH value. Compared with the CK group, the CEC of the red soil treated with M and M-HA-P increased by 9.5% and 64.4%, respectively. This shows that these treatments effectively improved the fertilizer retention capacity of red soil. The total amount of exchangeable bases in the soil is composed of four different cations, specifically, calcium, magnesium, potassium and sodium ions. Compared with the CK group, the application of M and M-HA-P significantly increased the total amount of exchangeable bases in the red soil, increasing by 17.9% and 77.6%, respectively. Specifically, the exchangeable calcium ions in the red soil increased by 13.0% under both treatments; the exchangeable magnesium ions increased by 18.2% and 9.09%, respectively; and the exchangeable potassium ions increased by 150% and 1500%, respectively. Compared with the CK group (0 cmol / kg), the exchangeable sodium ion concentrations in the red soil increased to 0 and 1.4 cmol / kg after the M and M-HA-P treatments, respectively. At the same time, compared with the CK group (91.7%), the base saturation of the red soil treated with M and M-HA-P increased by 7.4% and 7.7%, respectively. These results indicate that the application of M and M-HA-P effectively promoted the accumulation of exchangeable base ions in red soil, among which the effect of M-HA-P was more significant.
[0125] like Figure 6As shown in the figure, the exchangeable acid of red soil is mainly composed of hydrogen ions and aluminum ions. Compared with the CK group (0.25 cmol / kg), the amount of exchangeable acid in the red soil treated with M-HA-P decreased significantly, by 28.0%. This change was mainly due to the significant reduction in the content of exchangeable aluminum ions, which decreased by 57.1%. In addition, the M treatment almost completely removed the exchangeable acid. Compared with the acid-base buffering capacity of the red soil in the CK group (3.20 mmol / kg), both the M and M-HA-P treatments significantly enhanced the buffering capacity of the red soil, increasing by 23.4% and 22.2%, respectively. At the same time, these two materials also significantly increased the alkali production of the red soil, increasing by 5.61 mmol / kg and 4.85 mmol / kg, respectively, thereby effectively enhancing the alkalinity of the soil. The effective silicon concentration in the red soil of the CK group was 1.74 cmol / kg. After treatment with M and M-HA-P, the effective silicon content increased significantly by 677% and 148%, respectively.
[0126] (4.4) Relationship between exchangeable acid neutralization and silicon / exchangeable base ion release
[0127] The release of available silicon, the release of exchangeable base ions, and the consumption of exchangeable acid were calculated by measuring the difference in the content of the corresponding components in the red soil of the M and M-HA-P treatment groups and the control group (CK). Figure 7 As shown in Figure 2, there is a high linear correlation between the available silicon released by the materials and the consumption of exchangeable acid in red soil (R 2 =0.99), and the corresponding linear regression model is y=47.6x-0.46. The correlation between the release of exchangeable base ions and the consumption of exchangeable acid is almost negligible (R 2 =0.00). This indicates that in red soil, the reduction of exchangeable acid is mainly dominated by the silicon released by the material and the corresponding alkaline substances.
[0128] (4.5) Effects of materials on red soil clay mineral composition and cadmium, lead and zinc toxicity
[0129] In order to study the effect of mineral passivators and mineral-organic-phosphorus composites on the clay mineral composition of red soil, the clay minerals of red soil were first identified in detail, which laid the foundation for the subsequent qualitative and quantitative analysis. Three treatment methods were implemented on the red soil: natural drying (N), 55℃ ethylene glycol vapor treatment (EG) and 500℃ high temperature treatment (T). XRD analysis showed that the characteristic peaks at 1.40nm, 1.36nm, 1.00nm and 0.72nm corresponded to vermiculite (V), illite-vermiculite mixed layer (IV), illite (I) and kaolinite (K), respectively, as shown in Figure 2. Figure 8As shown, after being saturated with ethylene glycol and heated to 500 °C, the characteristic peaks of vermiculite and illite-vermiculite mixed layers are almost invisible. At the same time, the characteristic peaks of illite and kaolinite are relatively stable among the three treatments, indicating their strong ionic bonding ability.
[0130] XRD patterns revealed the effects of different treatments on the content of clay minerals in red soil, manifested as the intensity changes of clay minerals in each treatment group. The clay minerals extracted by centrifugation and sedimentation methods were then used for quantitative analysis by XRD technology. The analysis results showed that the relative abundances of 2:1 type clay minerals (illite, vermiculite and illite-vermiculite mixed layers) under different treatments were ranked as: CK < M < M-HA-P, among which the M-HA-P treatment showed the most obvious transformation effect. Specifically, the contents of 2:1 type clay minerals in red soil were increased by 2% and 4% in the M and M-HA-P treatments respectively, while the contents of kaolinite (1:1 type clay mineral) decreased by 2% and 4% correspondingly. These data indicate that the application of M and M-HA-P promoted the transformation of kaolinite to 2:1 type clay minerals in red soil. M-HA-P particularly significantly increased the content of illite-vermiculite mixed layers by 7%. The M treatment promoted the transformation to illite and vermiculite, increasing the contents of these two minerals by 3% and 2% respectively.
[0131] In the surface soil of paddy fields, the alternation of anoxic and aerobic environments leads to fluctuations in the redox potential, affecting the valence ratio of Fe in red soil. This fluctuation promotes the formation of highly active soluble Fe in red soil 2+ and colloidal Fe 3+ . At the same time, the application of mineral passivators and mineral-organic-phosphorus composites supplemented the missing alkali metals (potassium and sodium ions), alkaline earth metals (calcium and magnesium ions) and available silicon to red soil. These supplemented mineral nutrients promoted the transformation of kaolinite to 2:1 type clay minerals, including Fe 2+ and Mg 2+ substituting Al in the crystal lattice 3+ , as well as Fe 3+ reduction and K + fixation. This process occurs rapidly due to high electron transfer efficiency and is not limited by the overall reaction kinetics. Compared with 1:1 type clay minerals, 2:1 type clay minerals have a larger surface area, interlayer distance and CEC. Therefore, the increase in the content of 2:1 type clay minerals in red soil significantly enhanced the adsorption and fixation ability of red soil to cadmium, lead and zinc and the nutrient retention ability.
[0132] Analyze the toxicity of cadmium, lead and zinc in red soil by the TCLP method, such as Fig. 9As shown. The toxic cadmium, lead and zinc concentrations in red soil in CK were 4.60 mg / kg, 117 mg / kg and 251 mg / kg, respectively. After adding M and M-HA-P, the toxic concentrations of cadmium, lead and zinc in red soil decreased significantly. Specifically, the cadmium concentration decreased by 19.6% and 32.6%, the lead concentration decreased by 39.8% and 75.8%, and the zinc concentration decreased by 40.4% and 11.0%, respectively. These data show that the application of mineral passivators and mineral-organic-phosphorus composite materials can significantly reduce the toxicity of cadmium, lead and zinc in red soil. For cadmium and lead, the toxicity reduction effect of M-HA-P is better than that of M, while the toxicity reduction effect of zinc is better than that of M.
[0133] (4.6) SEM-EDS, FTIR and XPS analysis
[0134] The images taken by SEM show that the red soil surface of the CK group presents a smooth lamellar structure, such as Fig.10 As shown. After the M treatment, small round particles appeared on the surface; after the M-HA-P treatment, the surface was covered with more granular substances. These new features may be related to the precipitation and chelation of cadmium, lead and zinc, as well as mineral phase changes. EDS analysis shows that the red soil surface mainly contains oxygen, silicon, aluminum, potassium, phosphorus and iron elements, as well as trace amounts of lead and zinc. Although the red soil is severely contaminated by cadmium, lead and zinc, the cadmium content is extremely low and has not been detected by EDS. After treatment, the relative contents of oxygen, silicon, aluminum, potassium, calcium, magnesium, phosphorus and iron on the red soil surface increased.
[0135] FTIR analysis revealed that in the red soil samples treated with M and M-HA-P, the silicon (aluminum)-oxygen-silicon and oxygen-silicon (aluminum)-oxygen vibration bands changed compared with those in the CK group, which may be due to the precipitation of silicate, aluminate and aluminosilicate with cadmium, lead and zinc, such as Fig.11 At the same time, the silicon (aluminum)-hydroxyl, carbon-carbon, carbon-oxygen, carbon-hydroxyl and carbon-hydrogen vibration bands in the treated red soil also showed differences in intensity or wavelength compared with the CK group, indicating that these chemical bonds or functional groups may be involved in the stabilization process of cadmium, lead and zinc.
[0136] XPS analysis revealed that red soil is composed of oxygen, iron, potassium, calcium, magnesium, carbon, silicon, phosphorus and aluminum, while cadmium was not detected due to its extremely low content. Fig.12As shown. Lead ions mainly exist in the form of lead silicate (44.0%) and lead silicate / lead complex / lead hydroxide / lead phosphate / lead sulfate (56.0%). The main forms of zinc ions include zinc aluminate (34.1%) and zinc complex / zinc silicate / zinc hydroxide (65.9%). Compared with CK, the characteristic peak intensity and binding energy of lead and zinc in red soil after M-HA-P treatment changed significantly, and the characteristic peak of zinc also changed significantly after M treatment, indicating that these materials have a significant effect on the fixation of heavy metals in red soil. 4f of lead 5 / 2 With 4f 7 / 2 The energy level difference is 4.9 eV, suggesting that lead ions may form coordination bonds with red soil and mineral-organic-phosphorus composite materials. The main forms of oxygen ions include carbon-oxygen bonds / phosphates / silicates / metal oxides / sulfates / hydroxides and metal oxides / phosphates / hydroxides. After adding materials, the binding energy and percentage of the O1s peak changed significantly, reflecting the transformation of the forms of oxygen compounds in red soil.
[0137] like Fig.13As shown in the figure, compared with the CK group, the characteristic peak areas of carbonyl and peroxycarbonyl in the red soil samples treated with M and M-HA-P increased by 2.9% and 0.2%, respectively. At the same time, the characteristic peak areas of carbon-oxygen single bonds and carbon-oxygen-carbon bonds also increased, changing by 4.9% and 1.3%, respectively. In contrast, the characteristic peak areas of carbon-carbon single bonds, carbon-carbon double bonds, and carbon-hydrogen bonds decreased by 7.8% and 1.5%, respectively. These changes should be due to the complexation between carboxyl (-COOH), ester (-COO-), hydroxyl (-OH) and ether bonds (-O-) and cadmium, lead, and zinc, as well as the interaction between cadmium, lead, and zinc ions and π electrons. The main forms of potassium ions on the surface of red soil include potassium hydroxide, potassium sulfur oxide, potassium phosphate, potassium aluminate, and potassium silicate. After adding M, the characteristic peaks of potassium ions in red soil showed significant changes in binding energy and intensity, suggesting that the chemical state of potassium ions may have undergone a transformation. The main forms of calcium ions on the surface of red soil include calcium oxide (33.9%), calcium aluminum oxide (32.3%), and calcium silicon oxide / calcium sulfur oxide / calcium phosphate / calcium hydroxide (33.7%). The main forms of magnesium ions include magnesium silicon oxide / magnesium hydroxide (29.7%) and magnesium oxide / magnesium silicon oxide / magnesium hydroxide / magnesium aluminum oxide (70.3%). After adding M and M-HA-P, the characteristic peak area ratio, binding energy and strength of calcium ions and magnesium ions in red soil changed significantly, suggesting that the chemical state of calcium ions and magnesium ions may have undergone a transformation. Before and after the restoration treatment, calcium ions and magnesium ions in red soil exist in crystalline and non-crystalline forms (hydroxides). Silicon ions are mainly present in aluminosilicate / silicate (33.8%) and organosilicon compounds / silicate (66.2%). Phosphorus ions are mainly present in the form of metaphosphate (33.8%) and lead phosphate / cadmium phosphate / pyrophosphate / phosphate / organophosphorus compounds (66.2%). After adding M and M-HA-P, the characteristic peaks of silicon ions and phosphorus ions in the red soil showed obvious changes in binding energy or intensity, which may indicate that the chemical forms of silicon ions and phosphorus ions have changed. After the restoration treatment, the characteristic peaks of mineral nutrition in the red soil almost all experienced significant changes in percentage, intensity or position, which suggested that potassium, calcium and magnesium ions may have exchanged with cadmium, lead and zinc ions. At the same time, silicates and phosphates may have formed insoluble precipitates with cadmium, lead and zinc.
[0138] (4.7) Synergistic mechanism of cadmium, lead and zinc compound pollution remediation and red soil improvement
[0139] Cadmium, lead and zinc pollution control: The applied mineral-organic-phosphorus composite material significantly changed the chemical state of cadmium, lead and zinc in red soil. With its numerous active adsorption sites, the mineral-organic-phosphorus composite material enhances the capture, chelation, π-cation interaction, chemical precipitation and ion exchange of cadmium, lead and zinc ions. The combined effect of these effects effectively reduces the active content of cadmium, lead and zinc and improves their chemical stability. Specifically, the large specific surface area and abundant active sites of the mineral-organic-phosphorus composite material provide more capture opportunities for cadmium, lead and zinc ions, significantly improving the capture effect. Active functional groups such as carboxylic acid (-COOH), ester (-COO-), alcohol (-OH) and ether bond (-O-) in the material can form stable chelates with cadmium, lead and zinc ions. The aromatic ring structure in lignite humic acid (HA) constructs a stable adsorption mixture through the interaction of π-electrons with cadmium, lead and zinc ions, significantly enhancing the bonding strength between cadmium, lead and zinc and the material surface. At the same time, the active mineral components (phosphorus minerals, silicon minerals, aluminum minerals and silicon-aluminum minerals) in the material react with cadmium, lead and zinc ions to form insoluble stable compounds. This change is achieved through chemical precipitation. The difference is that XPS analysis reveals the phenomenon of sulfate reacting with lead ions to form lead sulfate precipitation, while the experimental results of the five-step extraction method show that after adding the mineral-organic-phosphorus composite material, the interaction between cadmium, zinc ions and iron and manganese oxides in red soil is enhanced. The application of mineral-organic-phosphorus composite materials also increases the alkalinity of red soil, helps to form hydroxide precipitation of cadmium, lead and zinc, and reduces the mobility of heavy metals. At the same time, cadmium, lead and zinc ions undergo ion exchange with cations such as potassium, calcium, magnesium and sodium in the material. Therefore, the application of mineral-organic-phosphorus composite materials enhances the stabilization effect on cadmium, lead and zinc, and reduces the bioavailability and mobility of cadmium, lead and zinc.
[0140] Nutrient supplementation and soil improvement: On the one hand, the alkaline metal ions and silicon ions in the mineral-organic-phosphorus composite material, especially calcium ions and magnesium ions, play a key role in red soil. The metal ions released by these active minerals react efficiently with the hydrogen ions and aluminum ions in the red soil to produce hydroxide ions, thereby neutralizing the acidity of the red soil and promoting the natural increase of pH value, reducing the harmfulness and mobility of cadmium, lead and zinc. The reduction of exchangeable acid in red soil is mainly driven by silicate minerals and corresponding alkaline components released by the mineral-organic-phosphorus composite material. Silicon ions mainly exist in the form of silicate or aluminosilicate minerals, which react with hydrogen ions in red soil to generate silicate ions and water, further consuming protons and increasing pH value. This process not only reduces the content of exchangeable acid in red soil and increases alkalinity, but also significantly enhances the acid-base buffering capacity and alkali production of red soil, improves the soil's resistance to acid-base changes, and effectively maintains the balance of pH value, which is extremely critical to the health of the soil and the growth of plants. On the other hand, the application of mineral-organic-phosphorus composite materials significantly promoted the transformation of kaolinite (1:1 type clay mineral) to illite-vermiculite mixed layer (2:1 type clay mineral) in red soil. This change not only increased the specific gravity of 2:1 type clay minerals, but also significantly improved the capture and stabilization of cadmium, lead and zinc in red soil due to its large specific surface area and CEC. Inorganic nutrients in active minerals, including potassium, calcium, magnesium, silicon and phosphorus, not only provide necessary nutrients for plants, but also promote the evolution of clay minerals. At the same time, lignite humic acid also provides additional organic nutrients. Ferrous ions and magnesium ions jointly promote the evolution of kaolinite to 2:1 type clay minerals through mechanisms such as replacement of aluminum ions in the lattice, reduction of iron ions and fixation of potassium ions. This evolution not only enhances the red soil's ability to stabilize cadmium, lead and zinc, but also improves the nutrient retention function of red soil, enhancing the fertility and structural stability of red soil. The interaction between nutrient supplementation and the evolution of clay minerals further enhanced the red soil's ability to capture cadmium, lead and zinc, achieving the dual goals of nutrient replenishment and soil improvement.
[0141] These combined effects not only directly reduce the bioavailability of cadmium, lead and zinc, but also indirectly strengthen the stabilization of red soil on cadmium, lead and zinc by increasing soil pH and promoting the transformation of clay minerals. At the same time, proton consumption and cation exchange processes enhance the alkalinity and pH buffering capacity of red soil, further reducing the risk of cadmium, lead and zinc diffusion. This combined effect not only controls the combined pollution of cadmium, lead and zinc, but also strengthens the natural buffer system of the soil, restoring the original ecological characteristics of red soil and providing a guarantee for the health and ecological balance of red soil.
[0142] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a mineral-organic-phosphorus composite material, comprising the following steps: The mineral raw materials are wet ball-milled and then roasted to obtain a mineral passivator; the mineral raw materials include, by mole fraction, 1 to 3 parts of illite, 0.5 to 2 parts of wollastonite, 0.5 to 2 parts of gypsum, 2 to 4 parts of dolomite, and 0 to 20 parts of calcium carbonate; The mineral passivator, humic acid, water-soluble phosphate and water are mixed and then aged and crystallized to obtain a mineral-organic-phosphorus composite material; the mass ratio of the mineral passivator to the humic acid is 1:0.1-7; the content of phosphorus in the mixture of the mineral passivator, humic acid and water-soluble phosphate is 1-16wt%.
2. The preparation method according to claim 1, characterized in that: The mixing comprises: subjecting the mineral passivator, humic acid and water to a first wet ball milling to obtain a first ball milling mixture; and subjecting the first ball milling mixture and water-soluble phosphate to a second wet ball milling.
3. The preparation method according to claim 2, characterized in that: The ball milling beads used in the first wet ball milling and the second wet ball milling respectively include large ball milling beads, medium ball milling beads and small ball milling beads; The diameter of the large ball milling beads is 1.3-2 cm, the diameter of the medium ball milling beads is 0.8-1.2 cm, and the diameter of the small ball milling beads is 0.1-0.6 cm; The ratio of the number of the large ball milling beads to the number of the medium ball milling beads is 1:0.5-2, and the ratio of the number of the large ball milling beads to the number of the small ball milling beads is 1:0.5-2; The ball-to-material ratios of the first wet ball milling and the second wet ball milling are independently 3 to 6:15 g.
4. The preparation method according to claim 2 or 3, characterized in that: The rotation speed of the first wet ball mill is 140 to 340 r / min, and the time of the first wet ball mill is 0.6 to 2.1 h; The rotation speed of the second wet ball mill is 140-340 r / min, and the time of the second wet ball mill is 0.3-2.3 h.
5. The preparation method according to claim 1, characterized in that: The temperature of the aging crystallization is 50-100° C. and the time is 8-25 hours.
6. The preparation method according to claim 1, characterized in that: The wet ball milling includes: performing a third wet ball milling on the mineral raw material and water.
7. The preparation method according to claim 6, characterized in that: The mass ratio of the mineral raw material to water is 1:0.2-0.9; The third wet ball milling beads include large ball milling beads, medium ball milling beads and small ball milling beads; The diameter of the large ball milling beads is 1.3-2 cm, the diameter of the medium ball milling beads is 0.8-1.2 cm, and the diameter of the small ball milling beads is 0.1-0.6 cm; The ratio of the number of the large ball milling beads to the number of the medium ball milling beads is 1:0.5-2, and the ratio of the number of the large ball milling beads to the number of the small ball milling beads is 1:0.5-2; The ball-to-material ratio of the third wet ball mill is 3 to 6:15 g; The rotation speed of the third wet ball milling is 140-340 r / min, and the time of the third wet ball milling is 0.3-2.3 h.
8. The preparation method according to claim 1, characterized in that: The calcination temperature is 950-1150° C., and the heat preservation time is 0.6-2.1 h.
9. The mineral-organic-phosphorus composite material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the mineral-organic-phosphorus composite material according to claim 9 in remediation of heavy metal contaminated soil.
Citation Information
Patent Citations
Mineral adsorbent as well as preparation method and application thereof
CN113522230A